Peroxymonosulfate activation based on Co9S8@N−C: A new strategy for highly efficient hydrogen production and synchronous formaldehyde removal in wastewater. (10th November 2022) - Gao, Caiyan; Feng, Xuezhen; Yi, Lian; Wu, Xiaoyong; Zheng, Renji; Zhang, Gaoke; Li, Yubiao
Highlights: Peroxymonosulfate (PMS) activation technology has been innovatively introduced. PMS/Co9 S8 @N−C system has presented nice performance for hydrogen production. DFT calculation and EPR test give a deep insight into the mechanism. The influence of parameters on the formaldehyde degradation are detailed investigated. Abstract: Formaldehyde (FA), as an important chemical raw material, has been widely used in many fields. However, the discharge of a large amount of FA-containing wastewater poses a serious threat to the environment and human health. Recently, the in-situ hydrogen energy release technology of hydrogen-containing stable liquid has been extensively explored due to its safe storage. Exploring a robust method to achieve FA removal and synchronous in-situ hydrogen release from FA containing wastewater is of great significant for environmental protection and energy crisis alleviation. Here, we have innovatively introduced peroxymonosulfate (PMS) activation technology into FA removal and hydrogen production simultaneously. The composite of nitrogen doped carbon coating Co9 S8 nanotubes (Co9 S8 @N−C) is employed as a proof of concept for FA decomposition and simultaneously hydrogen production based on PMS activation system. As expected, the Co9 S8 @N−C/PMS system presents much superior hydrogen production efficiency and satisfactory FA removal rate towards FA wastewater than those of common catalysis, photocatalysis and Fenton reaction in the basic condition in a wide range of FA concentration. The hydrogen yield reaches a value as high as 471 μmol within 60 min, corresponding to a FA degradation rate of 30% with an initial FA concentration of 0.722 mol L −1 . Characterizations and density functional theory (DFT) calculations suggest that the free radical process dominated by superoxide radical (O2 ⋅ − ) and nonradical process dominated by singlet oxygen ( 1 O2 ), which are induced by Co9 S8 @N−C/PMS system, are responsible for highly efficient hydrogen production via FA degradation. These generated O2 ⋅ − and 1 O2 can extract ⋅ H from FA to form ⋅ OOH intermediate, which can further combine with the ⋅ H from water to produce hydrogen. This study provides an applicable technique for environmental purification and new energy development based on FA containing wastewater.